2020
DOI: 10.3389/fmicb.2020.01623
|View full text |Cite
|
Sign up to set email alerts
|

Dual Repressive Function by Cip1, a Budding Yeast Analog of p21, in Cell-Cycle START Regulation

Abstract: Cip1, a newly identified yeast analog of p21, is a Cln3-CDK inhibitor that negatively regulates cell-cycle START. However, its function remains poorly understood. In this study, we found that deletion of CLN3 did not result in bypass of G1-phase arrest caused by Cip1 overexpression. Cip1 depletion in cln3 -null mutants significantly advanced the timing of Cln2 expression, supporting the idea that Cip1 represses START in a Cln3-independent manner. We set to search f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…p21 was first identified as a downstream gene of p53, subsequent research showed that p21 functions as an important cell cycle regulator, involved in the process of cell growth, differentiation, aging and death 21 . Previous studies have established that p21 can arrest the cell cycle in the G1 phase by interacting with cyclin D/CDK 22,23 . In our study, over‐expressed RACK1 led to p21 expression down‐regulation without affecting the expression of p53, indicating that p21 functions in an independent way on p53 in the development of CC with RACK1 dysregulation.…”
Section: Discussionsupporting
confidence: 48%
“…p21 was first identified as a downstream gene of p53, subsequent research showed that p21 functions as an important cell cycle regulator, involved in the process of cell growth, differentiation, aging and death 21 . Previous studies have established that p21 can arrest the cell cycle in the G1 phase by interacting with cyclin D/CDK 22,23 . In our study, over‐expressed RACK1 led to p21 expression down‐regulation without affecting the expression of p53, indicating that p21 functions in an independent way on p53 in the development of CC with RACK1 dysregulation.…”
Section: Discussionsupporting
confidence: 48%
“…S3 A ). In addition, if Cip1 were a CDK substrate, we would expect that G1 cyclin/CDK complexes would regulate its activity since Cip1 functions at the G1/S transition ( 24 , 33 , 41 ). However, G1 cyclin/CDK complexes are unable to phosphorylate Cip1 in vitro ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, it is associated with the occurrence of tumors and serves a role in the physiological and pathological processes. Previous studies have confirmed that p21 can form a complex with cyclin D/CDK to block the cell cycle in G1 phase and it can also interact with proliferating cell nuclear antigen (PCNA) via the C-terminus to block the activity of PCNA-activated DNA polymerase, thereby inhibiting DNA synthesis and arresting the cell cycle (55,56).…”
Section: Discussionmentioning
confidence: 99%